Perceived competences in everyday activities: Children's self-report and parents' and teachers' report using the first Austrian-German Perceived Efficacy and Goal Setting System (AG-PEGS) version / Einschätzungen kindlicher Kompetenzen in Alltagstätigkeiten durch Kinder, deren Eltern und Pädagogen/-innen, basierend auf der ersten deutschsprachigen PEGS (Perceived Efficacy and Goal Setting System)-Version - Costa Ursula Margarethe; Lindenthal Michael J. (Sciendo, 2015)
Introduction: A systems-oriented approach in contemporary health-care requires health professionals to include clients' and their proxies' perceptions to design specific, efficient, and cost-effective interventions. This influences the choice of appropriate methods and means for assessment and intervention. To learn more about the benefits of a systems-approach in assessment and intervention planning, there is a need to study how children and their proxies describe children's abilities. Aims: This study aimed to explore, describe, and compare perceived competences in everyday activities as reported by children with difficulties in their occupational performance, their parents and teachers, using the first Austrian-German version of the Perceived Efficacy and Goal Setting System (AG-PEGS). Method: Forty-two children, their parents and teachers completed the AG-PEGS. Data analysis included descriptive statistics, calculation of inter-rater agreement, differences between groups, and correlations between categories. Results: Overall, adults scored children's competences lower than the children themselves. Statistically significant differences of the perception of children, parents and teachers were found in single items, total scores and life areas (productivity, self-care, leisure), respectively. Differences in perceived competence were also found related to gender and schooling. Agreement in children's and adults' scorings varied depending on shared life areas (children and parents showing most agreement in self-care). Conclusion. Agreement and differences in perceived competences support the importance of children's and proxies' participation in assessment in order to gain a comprehensive picture and a better understanding of a child's situation and conditions, address a child's and his/her proxies' concerns, and provide individualized and context-relevant intervention. Children - assessment - self-efficacy - perceived competence - parents - teachers - participation